Expression of Low Affinity Nerve Growth Factor Receptor p75 in Classic Bladder Exstrophy - Promm, Martin; Otto, Wolfgang; Weber, Florian; Götz, Stefanie; Burger, Maximilian; Müller, Karolina; Rubenwolf, Peter; Neuhuber, Winfried; Roesch, Wolfgang H. (Frontiers in Pediatrics, 2021)
Successful primary closure of classic bladder exstrophy (BE) is crucial for development of bladder capacity and voided continence. It is universally agreed that an intensive pain management including the use of caudal epidural anaesthesia is an essential cornerstone for the outcome of this complex surgery. Whether and to what extent pain is caused by structural or functional changes is not yet known. The nerve growth factor (NGF) is regarded as a marker for pain in different bladder disorders. This prospective study investigated the role of histological alterations and NGF in patients with BE including 34 patients with BE and 6 patients with congenital vesicoureterorenal reflux (VUR) who served as controls. Between January 2015 and April 2020 transmural bladder biopsies were taken from the posterior bladder wall during delayed primary bladder closure. The samples were stained for histological evaluation and subjected to immunohistochemistry to analyze NGFR p75. Differences in histological alterations were examined with Fisher’s exact test, and Mann-Whitney-U-test was used to compare the NGFR p75 staining intensity between patients with BE and controls. Patients with BE showed significantly more often acute inflammation (p<0.001), squamous metaplasia (p=0.002), and cystitis glandularis (p=0.005) as well as NGFR p75 in the urothelium (p=0.003) than patients with VUR. A limitation of this study is the small number of participants due to the rare disease entity. Similar to other painful bladder disorders, pain transmission in BE after intitial closure may in part be facilitated by elevated NGF signaling through its receptor.